PENERAPAN SISTEM PENGENDALIAN MANAJEMEN DI MASA PANDEMI COVID-19 - Kristie, Viona Agnita; Andono, Fidelis Arastyo (Jurnal Akuntansi Kontemporer, 2022)
Research Purposes. The purpose of this research is to deeply investigate the MCS implementation and the possible changes/adjustments during the pandemic COVID-19 crisis in a company. Research Method. To deeply investigate the phenomenon, this research conducted a qualitative case study that used a company in food industrial sector.Research Result and Findings. The empirical findings depict that the changes in the working environment caused by the business strategy changes occurred as the response to the crisis. A more decentralised management control change should take place as the consequence of the changes. The adjustment or updating in more than one MCS tools alongside with the company’s leader as the key actor became the significant challenges for the company. This research contributes to the debate in MCS research, particularly during COVID-19 crisis time.